2022
DOI: 10.3389/fcvm.2022.865166
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Platelet Reactivity by Dual Therapy With Aspirin and Low-Dose Rivaroxaban in Peripheral Arterial Disease: A Pilot Study

Abstract: Patients with peripheral arterial disease (PAD) benefit from combination therapy with acetylsalicylic acid (ASA, 100 mg, one time per day) plus low-dose rivaroxaban (2.5 mg, two times per day) compared to ASA monotherapy. In particular, major adverse cardiac and limb events were significantly reduced after peripheral endovascular revascularization (EVR). In this pilot study, the platelet activation status in vivo and platelet reactivity in vitro were longitudinally analyzed by flow cytometric assays and calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The underlying mechanisms of DAT‐mediated attenuation in platelet reactivity to thrombin, however, remain unclear. A previous study found that in vitro treatment of human platelets with rivaroxaban and aspirin resulted in similar modulation in reactivity to the PAR‐1 activating peptide, TRAP‐6, but no effects were observed in the presence of thrombin 34 . This discrepancy may be because of species differences because PAR receptor subtypes (1‐4) have not been characterized in feline platelets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The underlying mechanisms of DAT‐mediated attenuation in platelet reactivity to thrombin, however, remain unclear. A previous study found that in vitro treatment of human platelets with rivaroxaban and aspirin resulted in similar modulation in reactivity to the PAR‐1 activating peptide, TRAP‐6, but no effects were observed in the presence of thrombin 34 . This discrepancy may be because of species differences because PAR receptor subtypes (1‐4) have not been characterized in feline platelets.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study found that in vitro treatment of human platelets with rivaroxaban and aspirin resulted in similar modulation in reactivity to the PAR‐1 activating peptide, TRAP‐6, but no effects were observed in the presence of thrombin. 34 This discrepancy may be because of species differences because PAR receptor subtypes (1‐4) have not been characterized in feline platelets. In addition, it is plausible that the PAR‐1 receptor may play a more prominent role in mediating platelet activation in cats because FXa has been shown to directly activate platelets via PAR‐1 in human platelets.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that aggregation may be inversely related to dosage, with higher doses associated with reduced platelet aggregation ( 25 ). A recent publication by Jurk et al ( 26 ) has also demonstrated that rivaroxaban reduces platelet activation through the PAR-1 receptor, a receptor for thrombin induced platelet activation ( 26 ). In our study, we demonstrated that there may be an additional mechanism of platelet inhibition by rivaroxaban through the arachidonic acid pathway, affecting the formation of pro-aggregatory TxA2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in the coagulation cascade, factor Xa has been identified as a direct agonist of PAR-1 leading to thrombin independent platelet activation and thrombus formation. By inhibiting factor Xa, rivaroxaban can attenuate platelet aggregation, in addition to its antithrombotic effect ( 7 , 8 , 38 , 39 ). In mice, administration of rivaroxaban for 20 weeks reduced thrombus formation and atherosclerotic plaque destabilization ( 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%